From Identity Denial to Racial Uplift Celebrating the Harlem Renaissance in Langston Hughes’ Not Without Laughter 1930 - HATTAB, Naima Nedjla (My University, 2020)
The Institution of Slavery, played an important role in the construction of America thanks to these Africans brought to the American coasts in order to enrich the economy of the colonies. Although the salverie was later abolished, many Americans born in America found themselves caught in the bonds of a white supremacist society that had little mercy for them. Indeed, the whites have succeeded in a procedure to keep the black population oppressed. For this particular reason, African Americans have sought to free themselves from white supremacy by elevating their race artistically and intellectually through song, art, literature, and politics. One of the most important movements to reassess the status of African Americans is known as the Harlem Renaissance. The latter, which saw the light of day in New York, more precisely in Harlem, has spread throughout American society in order to bring about all kinds of reforms that would participate in the revival of African folklore and remove blacks from stereotypes and ideologies. white. This research first aims to shed light on the historical context of this movement and the period that preceded it. Second, he takes Langston Hughes' novel "Not Without Laughs" as an example of what happened at that time. It will include the study of the portrayal of Harlem Renaissance in this novel, how it was described by the author, and how black people were excluded from American society.
Keywords: Literature; African Americans; Racial rise; Harlem Renaissance; Not without laughing at Langston Hughes; Denial of identity